Design and Building of Android Based Room Facility Lending Application - Dicky Giancini (IJCONSIST JOURNALS, 2020)
Android is a platform that is currently used by many users, so that almost every application created uses the Android platform because it is easy to use and also effective. The Faculty of Computer Science UPN "Veteran" East Java has 2 buildings and lots of rooms and other facilities such as laboratories, seminar rooms, and there are loans for equipment that can help the course of events whether in lectures or non- academics. Until now, the process of borrowing rooms and facilities at the Faculty of Computer Science is still done manually, such as using letters and several other processes. This also causes waste of paper and time because it is not necessarily the space or equipment that will be borrowed first by someone else. The purpose of designing and building a room facility loan application is to improve or optimize TU (Administration) services to room borrowers. The research methodology was carried out by collecting data such as interviews, literature study, observation and system design using the waterfall model. The results of this study are to facilitate services, be comfortable and safe in borrowing space.